The Canterbury tales - McCaughrean, Geraldine; Ambrus, Victor G.; Chaucer, Geoffrey, -1400. (Oxford [Oxfordshire] : Oxford University Press, 1984)
An illustrated retelling of Geoffrey Chaucer's famous work in which a group of pilgrims in fourteenth-century England tell each other stories as they travel on a pilgrimage to the cathedral at Canterbury.
Keywords: Chaucer, Geoffrey, -- -1400 -- Adaptations; Chaucer, Geoffrey, -- d. 1400 -- Adaptations; Christian pilgrims and pilgrimages -- England -- Canterbury -- Juvenile fiction; Middle Ages -- Juvenile fiction; Children's stories, English; Middle Ages -- Fiction; Short stories